Pengaruh Kinerja Keuangan Perusahaan, Reputasi Auditor Terhadap Opini Audit “Going Concern” Dengan Ukuran Perusahaan Sebagai Moderasi (Studi Pada Perusahaan Manufaktur Yang Terdaftar Bei Tahun 2019 – 2021) - Dewa Gde Valentino; Made Yenni Latrini (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to explore the correlation between financial performance, company size, and auditor reputation and going concern audit opinion. Sampling was carried out using a purposive sampling method, where the population that met certain criteria was selected as the sample. The object of this research is going concern audit opinion which is influenced by the company's financial performance, company size and auditor reputation. The research population consisted of 204 manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2021 period. The research results show that the company's financial performance and auditor reputation have a negative influence on going concern audit opinion. Meanwhile, company size can significantly moderate the influence of financial performance variables on going concern audit opinion. This research confirms the application of agency theory in the context of the relationship between company size, financial performance, and auditor reputation and going concern audit opinion. Keywords: Going Concern; Company Financial Performance; Auditor Reputation; Company Size